2020
DOI: 10.1007/s00220-020-03895-x
|View full text |Cite
|
Sign up to set email alerts
|

Singularity of the Spectrum for Smooth Area-Preserving Flows in Genus Two and Translation Surfaces Well Approximated by Cylinders

Abstract: We consider smooth flows preserving a smooth invariant measure, or, equivalently, locally Hamiltonian flows on compact orientable surfaces and show that, when the genus of the surface is two, almost every such locally Hamiltonian flow with two non-degenerate isomorphic saddles has singular spectrum. More in general, singularity of the spectrum holds for special flows over a full measure set of interval exchange transformations with a hyperelliptic permutation (of any number of exchanged intervals), under a roo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…zero) class of locally Hamiltonian flows in U min for which the Poincaré section can be chosen to be a selfsimilar interval exchange transformation 9 and restrict the observable f to belong to an infinite dimensional (but finite codimension g) space. For extensions of flows in this special class, though, we could provide a complete description of the ergodic behavior and prove a dichotomy between ergodicity and reducibility.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…zero) class of locally Hamiltonian flows in U min for which the Poincaré section can be chosen to be a selfsimilar interval exchange transformation 9 and restrict the observable f to belong to an infinite dimensional (but finite codimension g) space. For extensions of flows in this special class, though, we could provide a complete description of the ergodic behavior and prove a dichotomy between ergodicity and reducibility.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For some flows in genus one with a degenerate singularity (sometimes known as Kochergin flows), Forni, Fayad and Kanigowski could recently, prove in [12] that the spectrum is countably Lebesgue. The first typical spectral result for surfaces of higher genus, namely g ≥ 2 was recently proved by Chaika, Kanigowski and the authors, who showed in [9] that a typical locally Hamiltonian flow on a genus two surface with two isomorphic simple saddles has purely singular spectrum.…”
Section: Definitions Background Materials and Reductionsmentioning
confidence: 99%
“…Thus it remains to check the Condition 1 in Proposition 1.4. For this purpose, we consider the following result which follows from [5,Lemma 4.6]. Lemma 3.11.…”
Section: Proof Of the Skew-products Ergodicitymentioning
confidence: 99%
“…On the other hand, understanding more subtle spectral properties of locally Hamiltonian flows seems to be still in its infancy. Only recently the first results have appeared for the singular spectrum in [3] and the countable Lebesgue spectrum in [6].…”
Section: 11mentioning
confidence: 99%